RELIKT SĄDOWNICTWA ŚREDNIOWIECZNEGO – O JURYSDYKCJI WOJEWODY PŁOCKIEGO NAD SZLACHTĄ W POŁOWIE XVII W. - Moniuszko, Adam (Zeszyty Prawnicze, 2016)
A RELIC OF THE MEDIEVAL COURT SYSTEM: A JURISDICTION OF PLOCK VOIVOD OVER THE LOCAL NOBILITY IN THE MIDDLE OF THE 17TH CENTURY Summary This article concerns organisation and functioning of Plock voivod’s court and its jurisdiction over the nobility in the middle of the 17th century. Generally, this type of jurisdiction declined in the late Medieval period and Plock voivodship was the exception. The petty nobility without a privilege of ius non responsivum to monarch’s officials was submitted to this court. Analysis of three, previously unknown, voivod’s court records from period 1645 – 1650 enabled to show some details of this jurisdiction. Basically, its organisation was parallel to Plock land court in terms of division into two separate courts for each land of the voivodship and system of three sessions a year in every county (powiat). Material jurisdiction, which contained civil cases in old-Polish law sense, was likewise similar. Voivod’s court was a lower instance and the parties could appeal to the Crown Tribunal. Jurisdiction was exercised by a voivod’s judge, an official nominated by the voivod. Apart from deciding matters of contestation, voivod’s court had also competences in non-litigious cases, i.e. accepting entries to the records of various legal actions. As far as the latter is concerned, the court was used not only by the gentry submitted to its jurisdiction, but the rest of the local gentry as well. A firm position of the Plock voivod’s court in the local administration of justice system by 1650 proves that it fell in decline not before the second half of 17th century or even later.